Performance Analysis of Employees at the Regional Secretariat of Tomohon City - Bukara, Junike; Sumual, Tinneke Evie Meggy; Tarore, Steven Vleike (AIBPM Publisher, 2024)
This study undertakes a comprehensive exploration of employee performance within the regional secretariat of Tomohon city. Employing a descriptive qualitative approach, the research involves five informants, utilizing observation, interviews, and documentation for data collection. The analysis follows a structured process of data reduction, presentation, and conclusion verification. The findings reveal suboptimal performance in carrying out main duties and functions by employees, as evidenced in the analysis of effectiveness and efficiency in staffing, knowledge, skills, and discipline within the general section of the Tomohon city regional secretariat. Notably, while some tasks are executed effectively and efficiently, others display shortcomings, impacting overall performance. The study also identifies knowledge gaps among employees, affecting the secretariat’s functional execution. Coordination issues and non-compliance with government regulations are evident in skills-related sub-focus areas. Additionally, a deficiency in employee initiative is observed, as some employees hesitate to discuss work-related problems or demonstrate proactive engagement. This study sheds light on critical areas requiring attention for enhancing employee performance in the regional secretariat of Tomohon city.